TRANSDUCERS 2009 - 2009 International Solid-State Sensors, Actuators and Microsystems Conference 2009
DOI: 10.1109/sensor.2009.5285636
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth orientation of carbon nanotube pillars by catalyst patterning in microtrenches

Abstract: We present a novel method for controlling the growth orientation of individual carbon nanotube (CNT) microstructures on a silicon wafer substrate. Our method controls the CNT forest orientation by patterning the catalyst layer used in the CNTs growth on slanted KOH edges. The overlap of catalyst area on the horizontal bottom and sloped sidewall surfaces of the KOH-etched substrate enables precise variation of the growth direction. These inclined structures can profit from the outstanding mechanical, electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, there is a less control over the vertical direction of the growth. This typically results in relatively large nonuniformities on the top surfaces of grown CNT forest structures, where stray CNT bundles can be randomly found on these surfaces, affecting the structural precision and integrity of the forests. Moreover, the uniformity of CNT forests is typically compromised when grown on relatively large substrates (with surface areas of a few mm 2 or greater). , Estimated values of height deviation across the top surface of CNT forest structures found in the literature are in the range of 34.8–689.8 μm/mm 2 . ,,, The nonuniformity of the grown height can result from several factors, including the nonuniformity in the growth catalyst itself, the spatial variation of process temperature, and the variation of local partial pressure of the precursor gas . The forest’s nonuniformity can also be related to the spatial distribution of the catalyst nanoparticles on the substrate, which in turn impacts the mechanical coupling between neighboring CNTs during the growth process and eventually affects the overall uniformity .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a less control over the vertical direction of the growth. This typically results in relatively large nonuniformities on the top surfaces of grown CNT forest structures, where stray CNT bundles can be randomly found on these surfaces, affecting the structural precision and integrity of the forests. Moreover, the uniformity of CNT forests is typically compromised when grown on relatively large substrates (with surface areas of a few mm 2 or greater). , Estimated values of height deviation across the top surface of CNT forest structures found in the literature are in the range of 34.8–689.8 μm/mm 2 . ,,, The nonuniformity of the grown height can result from several factors, including the nonuniformity in the growth catalyst itself, the spatial variation of process temperature, and the variation of local partial pressure of the precursor gas . The forest’s nonuniformity can also be related to the spatial distribution of the catalyst nanoparticles on the substrate, which in turn impacts the mechanical coupling between neighboring CNTs during the growth process and eventually affects the overall uniformity .…”
Section: Introductionmentioning
confidence: 99%
“…However, only single layer of planar VA-CNTs film was adopted as the structure, which was lacked of the design flexibility in the out-of-plane direction. Several processes in previous studies have been reported to fabricate complicated 3D CNTs structures [3][4][5]. Nevertheless, the additional multi-stepped pyrolysis [3], liquid-condensed capillary formation [4], and KOH-etched Si-trench [5] must be applied during these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several processes in previous studies have been reported to fabricate complicated 3D CNTs structures [3][4][5]. Nevertheless, the additional multi-stepped pyrolysis [3], liquid-condensed capillary formation [4], and KOH-etched Si-trench [5] must be applied during these processes. In addition to the growth of single-layered VA-CNTs film, various approaches have been developed to grow the multilayered VA-CNTs stacks by catalyst coinjection [6][7] and catalyst predeposition [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many promising applications of vertically aligned carbon nanotube (CNT) “forests” have been demonstrated, including biomimetic adhesives, elastic foams, filtration membranes, and thermal interfaces; however, the geometries of CNT forests and patterned microstructures have been largely restricted to simple vertical and sloped shapes, Nevertheless, we envision that an ability to make complex 3D microstructures out of CNTs, which are inspired by the geometry and applications of macroscale folded structures, could lead to further novel investigations. To this end, we present a method for high-throughput fabrication of corrugated three-dimensional (3D) CNT microstructures, enabling the engineering of novel multilevel architectures with both symmetric and asymmetric geometries.…”
mentioning
confidence: 99%